THE INDEPENDENT STUDY FUTURES AND SIGNIFICANCE (Modern education and development, 2024)
This article discusses the concept of independent learning, highlighting its significance in fostering self-motivation and responsibility for one's learning process. It explores different learning styles, such as visual, auditory, and kinesthetic, and emphasizes the importance of teacher support through strategies like scaffolding and feedback.